Heart bones ebook - Hoover, Colleen (2022)
From the #1 New York Times bestselling author of It Ends with Us and It Starts with Us ! Moving, passionate, and unforgettable, Colleen Hoover's novel follows two young adults from completely different backgrounds embarking on a tentative romance, unaware of what the future holds. After a childhood filled with poverty and neglect, Beyah Grim finally has her hard-earned ticket out of Kentucky with a full ride to Penn State. But two months before she's finally free to change her life for the better, an unexpected death leaves her homeless and forced to spend the remainder of her summer in Texas with a father she barely knows. Devastated and anxious for the summer to go by quickly, Beyah has no time or patience for Samson, the wealthy, brooding guy next door. Yet, the connection between them is too intense to ignore. But with their upcoming futures sending them to opposite ends of the country, the two decide to maintain only a casual summer fling. Too bad neither has any idea that a rip current is about to drag both their hearts out to sea.